Teaching And Assessing In Arts And Humanities Courses: Lessons From Inside The Classrooms Of Four Universities - Fernandes, Domingos (2015)
Research reported and discussed in this paper was developed within a wider three-year international research project (2011-2014) involving 36 researchers from four Portuguese and three Brazilian universities (The project has been financed by National Funds through Fundação para a Ciência e Tecnologia (FCT) -Foundation for Science and Technology – Project PTDC/CPE-CED/114318/2009.) In the last decades, students have been entering higher education as never before and the European universities have been faced with all sorts of challenges (e.g., quality education for all, student mobility, a growing scarcity of resources). Traditional teaching and assessment practices, mostly based upon the so-called telling paradigm, still predominant in higher education, have been questioned and under pressure to change. Indeed, research have been pointing out that students learn better when they are engaged in the learning processes and when assessment for learning is integral to the organisation and development of teaching (e.g. Biggs, 2006; Black & Wiliam, 2006). As a result, a framework aiming at transforming and improving pedagogy and curricular practices in higher education was formally and politically put forward as a consequence of the so-called Bologna process. Since then, there is a growing body of literature claiming that: a) there is a need for a greater integration of learning, teaching, and assessment; b) more attention should be put on the need to improve higher education teachers’ expertise in the teaching, learning, and assessment domains of knowledge; and c) there is empirical evidence showing that it is possible to improve higher education teachers’ pedagogical practices and students’ learning (e.g. Bryan & Clegg, 2006; Falchicov, 2005; Menges & Austin, 2001). In a literature synthesis of 30 empirical studies developed in a ten-year time span (2000-2009), Fernandes & Fialho (2012) concluded that new and innovative ways to assess students’ learning were related to profound changes in teaching practices. They also inferred that innovative assessment, namely assessment for learning, could only make sense if, for instances, students were provided with quality feedback, were engaged in finding solutions to a variety of tasks, interacted on a regular basis with their colleagues and their teachers, used self-assessments and different forms of “interactive assessments” (e.g., peer assessment, small-group assessment) to regulate their learning, and participated in the processes of curriculum decision-making at the classroom level. These and other results from research on pedagogy in higher education were used as a framework to study teachers’ teaching and assessment practices, an area that still needs further empirical investigation. Therefore, the overall purpose of the project was to describe, to analyse, and to interpret higher education teachers’ teaching and assessment practices in the context of real undergraduate classes. Moreover, the project studied both teachers’ and students’ perceptions on issues of teaching and assessment practices. Consequently, it enabled the establishment of a variety of relationships between what happened in real classes concerning a given issue (e.g., distribution of feedback; assessment tasks; teaching planning; students’ participation) and the overall perceptions of the participants about that same issue. Both teachers and students played a major role in this research endeavour, sharing their perceptions through interviews and questionnaires and welcoming researchers to observe their classes. As a whole, the project enabled research-based qualitative and quantitative analyses and comparisons. This paper emerged from research work that took place within the four Portuguese universities involved in the project and it was limited to the study of teaching and assessment practices in the context of undergraduate programmes of Arts and Humanities (e.g., Art History, Design, Languages and European Literatures, Music, Drawing). The other undergraduate programmes involved in the project were in the domains of Social Sciences, Health Sciences, and Sciences and Technology.